Klasterisasi Wilayah Kabupaten Jember Berdasarkan Tingkat Ketahanan Pangan - Fajrin Nurman Arifin; Oktalia Juwita (INFORMAL: Informatics Journal, 2022)
Food security is a condition of food proclamation based on the availability of sufficient food to be able to live a healthy, active and productive life in a sustainable manner. Based on data from the Global Food Security Index (GFSI), Indonesia is ranked 69th with a level of food availability with a value of 63.7% and a level of ability or food needs of 74.9%. Jember Regency as one of the regencies in East Java Province based on TP2AK food security data in 2020 is in good condition (very resistant). However, in the same year Jember Regency experienced natural disasters with a total of 92 incidents The World Food Program in 2009 explained that one of the indicators of food security is vulnerability to food insecurity which is influenced by natural disasters. Based on the disaster conditions experienced by Jember Regency, the research carried out is to group food security areas in the Jember Regency area based on transient indicators using the KMeans method. The results of the analysis of the optimal SSE cluster formed in K4 (4 clusters) with an SSE value of 24,809. Each of the 4 clusters formed has a food security category of very resistant, resistant, moderately resistant, and somewhat vulnerable.